Exploring the Impact of Merdeka Curriculum with Deep Learning Approach on English Language Teaching Practices in Indonesian Secondary Schools - Syakira, Salvia Neysa; Wijaya, Ismah Fitri; Rahmadani, Bhaswara; Eviyuliwati, Ismalianing (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2025)
This study explains the impact of the Merdeka Curriculum combined with a deep learning approach on English teaching methods at the Indonesian secondary school level. The data in this study were collected using qualitative methods, by collecting responses from 11 teachers using a Likert scale questionnaire and conducting semi-structured interviews with three teachers. The results of the study show that teachers consider the Merdeka Curriculum to be a more organized curriculum, particularly because of its simpler lesson planning framework and focus on conscious, enjoyable, and meaningful learning processes. Teachers also reported positive improvements in student participation and learning attitudes. However, there are still several major challenges related to the use of technology, self-learning, and self-discipline. In general, the shift from the Merdeka Curriculum to the Merdeka Curriculum with a Deep Learning Approach shows positive progress in teaching English.